FREACSIM - A Framework for Creating and Simulating Real-Time Capable Network on Chip Systems and Applications - Schönwetter, Dominik; Veldema, Ronald; Fey, Dietmar (EAI Endorsed Transactions on Internet of Things, 2015)
This paper presents the new Framework for Real-time capable Embedded system and ArChitecture SIMulation (FREACSIM), a highly configurable full-system simulation environment enabling and easing the modeling, simulation and verification of Network on Chip architectures for hard real-time systems. The framework is mostly geared towards software developers, supporting them in the simulation of NoCs at an instruction accurate level and offers a broad variety of real-world hardware components as part of the integrated virtualization toolbox. FREACSIM provides a software-based routing strategy between nodes, with a single node consisting of a processor and required peripherals for enabling real-time capability. This allows a flexible and independent comparison of currently implemented hardware strategies, as well as an easy adaption to better suit new hardware needs. The software-based routing, as well as distributed applications that can be implemented for the NoC hardware design, are able to use the real-time operating system eCos, which is part of our framework. As a result, real-time capable software can be implemented for, and tested on, complex NoC systems. We demonstrate the flexibility and the benefits of our framework with a set of applications (use cases), which cover typical heavy and light load distributions between communication and computation.